2009
DOI: 10.1002/rcm.4100
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of high‐precision continuous measurements of water vapor isotopologues in laboratory and remote field deployments using wavelength‐scanned cavity ring‐down spectroscopy (WS‐CRDS) technology

Abstract: This study demonstrates the application of Wavelength-Scanned Cavity Ring-Down Spectroscopy (WS-CRDS) technology which is used to measure the stable isotopic composition of water. This isotopic water analyzer incorporates an evaporator system that allows liquid water as well as water vapor to be measured with high precision. The analyzer can measure H2(18)O, H2(16)O and HD(16)O content of the water sample simultaneously. The results of a laboratory test and two field trials with this analyzer are described. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
258
3
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(270 citation statements)
references
References 18 publications
6
258
3
3
Order By: Relevance
“…Gupta et al [2009] found the same model Picarro instrument drifted by only 2.0 per mil in δD-equivalent to an approximate 0.25 per mil drift in δ 18 O-over a four week period. Similarly, Aemisegger et al [2012] detected a maximum drift in δ 18 O of 0.5 per mil over a 14 day ambient sampling period.…”
Section: Isotopic Calibrationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Gupta et al [2009] found the same model Picarro instrument drifted by only 2.0 per mil in δD-equivalent to an approximate 0.25 per mil drift in δ 18 O-over a four week period. Similarly, Aemisegger et al [2012] detected a maximum drift in δ 18 O of 0.5 per mil over a 14 day ambient sampling period.…”
Section: Isotopic Calibrationsmentioning
confidence: 79%
“…[10] The mixing ratio and isotope ratios were measured at 10 s frequency with a Picarro analyzer (the same instrument as Noone et al [2013]), which uses cavity-enhanced tunable diode laser absorption spectroscopy (Picarro model 1115-i [Gupta et al, 2009]). Submicron aerosol was measured across 99 diameter ranges spanning 55-1000 nm using a Particle Metrics Ultra-High Sensitivity Aerosol Spectrometer (UHSAS, now sold by Droplet Measurement Technologies, Boulder, CO) [Yokelson et al, 2007;Cai et al, 2008].…”
Section: Instrumentation and Configuration Of Sampling Platformmentioning
confidence: 99%
“…This process is very sensitive; however, it is also very time consuming [3]. With the advent of instrumenttation using off-axis integrated cavity output spectroscopy (OA-ICOS), such as the Liquid Water Stable Isoope Analyzer (LIWA) DLT-100 from Los Gatos Inc. or the L2130 from Picarro Inc., the time required to analyze samples is no longer the bottleneck in sample processing for stable isotope analysis [7]. Currently, the major bottleneck for studying stable isotopes has shifted to the time required for complete extraction of water from soil samples collected from the field [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, carbon dioxide concentrations as low as a few parts per million have been measured (13), using CRDS and the same technique has been used to determine 13 C/ 12 C isotope ratios (13)(14)(15)(16), for example, as a diagnostic for ulcer-forming bacteria (Helicobacter pylori) by CO 2 breath analysis (13). CRDS has also been used successfully to analyze hydrogen and oxygen isotopes in water samples, introduced under either a liquid or vapor form, with isotopic measurements that parallel the high-precision yielded with dual-inlet IRMS systems (17,18). Thus, CRDS is not intrinsically inferior to mass spectrometry for isotope ratio measurements, although the present study does not reach this precision.…”
mentioning
confidence: 99%